Prototype Implementation of Exhaust Fan Control Using Mamdani Fuzzy Logic to Minimize LPG Concentration - Hanafi, Mohamad Rizal; Adjhi, Dhimaz Purnama; Adiwilaga, Anugrah (Politeknik Negeri Semarang, 2024)
This research aims to design and build a prototype of LPG gas leak detection system using fuzzy logic Mamdani method based on ESP32 with MQ-2 and DHT11 sensors as input and exhaust fan as output or action taken to prevent gas concentration. This research methodology includes literature study, identification and analysis, data collection, design implementation, software and hardware testing, and experiments to verify system performance. The results show that the system can detect LPG leaks and then provide preventive action by adjusting the speed and turning on the exhaust fan. This research is a prototype LPG gas leak detection system using fuzzy logic can be a solution to prevent hazards due to leaking gas. The contribution of this research is to provide alternative data processing methods that can improve the performance of gas sensors and provide responses that are in accordance with environmental conditions.